Radiation Hazard Indices in Some Soil Samples from Uranium Mine in Abuskair, Iraq Using HPGe Detector - Hamed Al-Gazaly, Hussain (Asian Journal of Chemistry, 2016)
The specific activity of natural radioactive nuclei in 37 samples of soil taken from different sites around the uranium mine in Najaf province, Iraq, were studied. The experimental data were obtained using a high purity germanium (HPGe) detecting system. A standard source of g-ray (Eu-152) was used to calibrate the HPGe system. The detection time of the soil samples was 10,000 sec. Accordingly, the specific activity of the soil samples ranged from 27.4 to 920 Bq/kg for 238U, 5.1 to 14.5 Bq/kg for 232Th and 124 to 598 Bq/kg for 40K, with mean values of 88.849 Bq/kg, 9.79 Bq/kg and 284.65 Bq/kg, respectively. In order to assess the radiation hazards of the natural radioactivity, the radium equivalent activity (Raeq), the g-ray absorbed dose (D), the annual effective dose, the internal hazard index (Hin) and the external hazard index (Hex) were calculated and then compared with the standard published values for safe use (OECD, 1979) together with the world average values of UNSCEAR.